Measurement of differential cross sections of deuteron elastic scattering on 31P for EBS purposes - Bligoura, Natalia; Ntemou, Eleni; Aslanoglou, Xenophon; Kokkoris, Michael -; Lagoyannis, Anastasios; Maragkos, Fotis; Misaelides, Panagiotis; Patronis, Nikolaos; Preketes-Sigalas, Kostas (HNPS Advances in Nuclear Physics, 2020)
The 31P(d,d0)31P elastic scattering differential cross-sections were measured, for the first time, in the energy range Ed,lab=900-2400 keV, using a variable energy step, for elastic backscattering spectrometry (EBS) purposes. The measurements were performed at the 5.5 MV TN11 HV Tandem Accelerator of the N.C.S.R. “Demokritos”, implementing a high precision goniometer. The experimental setup consisted of five silicon surface barrier (SSB) detectors, placed at the laboratory scattering angles between 130° and 170° (in steps of 10°). The target used was a thin GaP layer evaporated on a self-supporting carbon foil. To validate the obtained results, benchmarking measurements were performed, using a polished GaP crystal. The determined cross-section datasets are compared with the corresponding ones using Rutherford’s formula, and similarities and discrepancies will be discussed and analyzed.